Charge localization in a diamine cation provides a test of energy functionals and self-interaction correction - Xinxin Cheng (Nature Portfolio, 2016)
Density functional theory is widely used throughout the chemical sciences, but suffers from over-emphasis on charge delocalisation. Here, the authors experimentally probe the energies of two states of a diamine cation and show how a self-interaction correction allows for the accurate prediction of both states.